Adenovirus VA RNAI: a positive regulator of mRNA translation. - Svensson, C (1984)
We have developed a sensitive transient expression assay in 293 cells to study the effect of VA RNAs on the translation of adenovirus mRNAs. Monolayers of 293 cells were transfected with mixtures of recombinant plasmids encoding adenovirus-specific transcription units and plasmids encoding VA RNAs. Transfected cells were labeled with [35S]methionine for ca. 15 h, and labeled cell extracts were prepared. Changes in the protein expression caused by VA RNA cotransfection were measured by immunoprecipitation, using monospecific antisera prepared against adenovirus-specific polypeptides. Using this experimental design, we demonstrate that VA RNAI stimulates the translation of both early and late adenovirus mRNAs. Synthesis of the E3 19,000-dalton glycoprotein and the E2A 72,000-dalton DNA binding protein was stimulated between 10 and 20 times by VA RNAI cotransfection. Synthesis of the late hexon polypeptide was also stimulated, although translation of hexon was from an aberrant mRNA lacking the second and third segments of the common tripartite leader attached to late adenovirus mRNAs. VA RNAII, although very homologous to VA RNAI, does not function as a translational stimulator.